Pion femtoscopy measurements in ALICE at the LHC - Kamil Graczykowski Łukasz (EPJ Web of Conferences, 2014)
We present the results of two-pion Bose-Einstein correlations measured in Pb–Pb collisions at a center-of-mass energy √sNN = 2:76 TeV recorded by ALICE at the Large Hadron Collider. These types of correlations allow to extract, using the technique of femtoscopy (also known as Hanburry-Brown Twiss interferometry, or shortly HBT), the space-time characteristics of the source from the correlation calculated as a function of the pair momentum difference. The femtoscopic analysis was performed using both the Spherical Harmonics decomposition and the standard 3D Cartesian representation of the correlation function. The source sizes in three dimensions, the HBT radii, were extracted by fitting the experimental correlation functions. The resulting dependencies of the radii as a function of centrality and pair transverse momentum are shown. The results indicate the existence of a flowing medium and provide constraints on existing dynamical models. The ALICE Pb–Pb HBT radii are also compared to the pp analysis and other heavy-ion experiments in order to test the multiplicity scaling between different systems.